It all comes down to this - English, Karen (Houghton Mifflin Harcourt, 2019)
In 1965, twelve-year-old Sophie is the only black child in an all-white neighborhood. Her sister Lily encourages Sophie to make friends, even by doing things she might be uncomfortable with, like playing tennis. But when trouble erupts in a nearby town, Sophie finds out how complicated her life really is.